2017
DOI: 10.1167/tvst.6.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Towards Treatment of Stargardt Disease: Workshop Organized and Sponsored by the Foundation Fighting Blindness

Abstract: Accumulation of fluorescent metabolic byproducts of the visual (retinoid) cycle is associated with photoreceptor and retinal pigment epithelial cell death in both Stargardt disease and atrophic (nonneovascular) age-related macular degeneration (AMD). As a consequence of this observation, small molecular inhibitors of enzymes in the visual cycle were recently tested in clinical trials as a strategy to protect the retina and retinal pigment epithelium in patients with atrophic AMD.To address the clinical transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 57 publications
0
60
0
5
Order By: Relevance
“…This was clearly evidenced by an enhanced NIR‐AF in the melanosomes in the subretinal pigmented cells of blue light‐exposed Abca4 −/− mice. Likewise, the increase in melanin‐dependent NIR‐AF was demonstrated in most ABCA4‐STGD1 patients . These findings together indicate that photo‐oxidation linked to the changes in fluorescence properties of pigment granules (melanin, lipofuscin, and melanolipofuscin), is a common mechanism of the STGD1 phenotype and blue light damage in Abca4 −/− mice.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This was clearly evidenced by an enhanced NIR‐AF in the melanosomes in the subretinal pigmented cells of blue light‐exposed Abca4 −/− mice. Likewise, the increase in melanin‐dependent NIR‐AF was demonstrated in most ABCA4‐STGD1 patients . These findings together indicate that photo‐oxidation linked to the changes in fluorescence properties of pigment granules (melanin, lipofuscin, and melanolipofuscin), is a common mechanism of the STGD1 phenotype and blue light damage in Abca4 −/− mice.…”
Section: Discussionmentioning
confidence: 59%
“…Likewise, the increase in melanin-dependent NIR-AF was demonstrated in most ABCA4-STGD1 patients. 70 These findings together indicate that photo-oxidation linked to the changes in fluorescence properties of pigment granules (melanin, lipofuscin, and melanolipofuscin), is a common mechanism of the STGD1 phenotype and blue light damage in Abca4 −/− mice. Loss of the RPE cells in the blue-light exposed mice was consistent with the reduction in the level of quantified bisretinoids by HPLC.…”
Section: Discussionmentioning
confidence: 81%
“…Several STGD1 treatment approaches including pharmacological, gene augmentation and stem cell-therapy are in early clinical phases, although there are currently no FDA-approved therapies [5,6]. The success of clinical trials evaluating efficacy is largely dependent on sensitive and reproducible outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have shown that in AMD the sensitivity of the rods decreases more rapidly than the sensitivity of the cones [21]. Although AMD and STGD1 are two different pathophysiological entities, they may share some common pathogenic features such as the photo-oxidative processes initiated by retinal pigment epithelium bisretinoids which could explain suggested links to light exposure in both STGD1 and AMD [6]. Hence, testing scotopic visual function may be indeed a promising additional outcome measure that may start to progress at a different stage of Data are presented as mean ± standard deviation (range).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation